Flexible Exchange Rate with Inflation Targeting in Chile: Experience and Issues - José De Gregorio; Andrea Tokman; Rodrigo Valdés (Inter-American Development Bank, Research Department, 2005)
The first five years of the flexible exchange rate and inflation targeting regime in Chile have shown positive results. Inflation is under control, the exchange rate has moved with the external conditions, monetary policy has been countercyclical and the cycle has apparently smoothened. Even though exchange rate volatility has increased, as expected with a flexible regime, this has also happened in other countries with similar characteristics. This increased volatility has lower extreme real exchange rate valuations than in the past, as is also seen in other countries with alternative exchange rate regimes. Important progress in derivatives market deepening, as well in a lower pass-through from the exchange rate to inflation, have contributed to increasing the credibility and feasibility of the current policy framework, while minimizing potential costs derived from that framework.
Keywords: 330; Flexibler Wechselkurs; Volatilität; Inflationssteuerung; Geldpolitik; Chile